PENGARUH PEMBENTUKAN MODAL KOTOR (GROSS CAPITAL FORMATION), KEBEBASAN EKONOMI DAN KEBEBASAN POLITIK TERHADAP PRODUK DOMESTIK BRUTO : ANALISIS ANTAR NEGARA - Danny Pratomo, Said Muhammad, Mohd. Nur Syechalad. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: This study aims to determine the effect of Gross Capital Formation (Gross Capital Formation), Economic Freedom and Political Freedom on Gross Domestic Product in the countries, and per capita income groups based on World Bank per capita income classification. The data used in this study is a secondary data sourced from World Development Indicators, World Bank, The Heritage Foundation, and The Freedom House in 2012. This study uses Ordinary Least Square method with cross section data. The results of the study used three independent variables showed mixed results at the level of α = 5%. For the Gross Domestic Product, Gross Capital Formation variable has a positive effect, negative effect on Economic Freedom variable and negative effect on Political Freedom variable. For low-income countries, Gross Capital Formation variable has a positive effect, positive influence on variables Economic Freedom and Political Freedom variable has a positive effect. And for high-income countries, Gross Capital Formation variable has a positive effect, negative effect on Economic Freedom variable and Political Freedom variable has a negative effect. Based on the analysis results, we can conclude that the diversity of the results obtained from the analysis conducted shows Gross Capital Formation, Economic Freedom and Political Freedom nature varies in each state and the state's per capita income brackets. This study is expected to be a reference material consideration in the planning and improvement of the Gross Domestic Product number of countries of the world. Keywords : Gross Domestic Product, Gross Capital Formation, Economic Freedom, Political Freedom. Abstrak : Penelitian ini bertujuan untuk mengetahui pengaruh Pembentukan Modal Kotor (Gross Capital Formation), Kebebasan Ekonomi dan Kebebasan Politik terhadap Produk Domestik Bruto pada negara-negara, dan golongan pendapatan per kapita. Data-data yang digunakan dalam penelitian ini adalah data sekunder yang bersumber dari World Development Indicator, World Bank, The Heritage Foundation, dan The Freedom House tahun 2012. Penelitian ini menggunakan metode Ordinary Least Square dengan data cross section. Hasil penelitian pada ketiga variabel independen yang digunakan menunjukkan hasil yang beragam pada taraf α = 5%. Untuk Produk Domestik Bruto, variabel Gross Capital Formation berpengaruh positif, variabel Kebebasan Ekonomi berpengaruh negatif, dan Kebebasan Politik berpengaruh negatif. Untuk low income countries, variabel Gross Capital Formation berpengaruh positif, variabel Kebebasan Ekonomi berpengaruh positif, dan Kebebasan Politik berpengaruh positif. Dan untuk high income countries, variabel Gross Capital Formation berpengaruh positif, variabel Kebebasan Ekonomi berpengaruh negatif, dan Kebebasan Politik berpengaruh negatif. Berdasarkan hasil analisis tersebut dapat disimpulkan bahwa keberagaman hasil yang diperoleh dari analisis yang dilakukan memperlihatkan Pembentukan Modal Kotor, Kebebasan Ekonomi dan Kebebasan Politik sifatnya sangat bervariasi pada tiap negara dan golongan pendapatan per kapita negara. Penelitian ini diharapkan dapat menjadi bahan rujukan dan pertimbangan dalam perencanaan peningkatan Produk Domestik Bruto sejumlah negara dunia. Kata Kunci : Produk Domestik Bruto, Pembentukan Modal Kotor (Gross Capital Formation), Kebebasan Ekonomi dan Kebebasan Politik.